Are miraculous gifts for today? four views - Gaffin, Richard B. Jr; Saucy, Robert L.; Storms, C. Samuel; Oss, Douglas A.; Grudem, Wayne A. 1948- (Grand Rapids, MI Zondervan, 1996)
Contents : Four views : Cessationist / Richard B. Gaffin, Jr; Open but cautious / R.L. Saucy; Third wave / C. Samuel Storms; Pentacostal/Charismatic / Douglas A. Oss. Includes bibliographical references and index.
Counterpoints